Integrative Conjugative Element ICEHs1 Encodes for Antimicrobial Resistance and Metal Tolerance in Histophilus somni - Bhatt, Krishna; Timsit, Edouard; Rawlyk, Neil; Potter, Andrew; Liljebjelke, Karen (Frontiers in Veterinary Science, 2018)
The objectives of this study were to determine antimicrobial resistance and metal tolerance, and identify associated genes and mobile genetic elements in clinical strains of Histophilus somni isolated from feedlot cattle in Alberta during years 2012-2016 (contemporary isolates, n=63) and years 1980-1990 (historical isolates, n=31). Comparison of antimicrobial resistance (AMR) showed a significant increase in resistance among contemporary isolates compared to historical isolates (P<0.001). Tolerance to copper (Cu) and zinc (Zn) concentrations above 1 mM was observed in 68% and 52% of the contemporary isolates, respectively. The tet(H) gene associated with oxytetracycline resistance and multicopper oxidase (mco) and cation efflux (czcD) genes associated with Cu and Zn tolerance were identified. An integrative conjugative element; ICEHs1, was identified in whole genome sequences of strains resistant to oxytetracycline, which had Cu and Zn minimum inhibitory concentrations (MIC) greater than 1 mM. The length of ICEHs1 was 64,932 bp and it contained 83 genes, including tetracycline resistance gene tetH, a multidrug efflux pump gene ebrB, and metal tolerance genes mco, czcD, and acr3. Comparative genomics of ICEs revealed that ICEHs1 shares high homology with previously described ICEs of Histophilus somni, Pasteurella multocida and Mannheimia haemolytica. The ICEHs1 is an active element capable of intra- and inter-genus transfer as demonstrated by successful transfer to H. somni and P. multocida recipients. All isolates carrying ICEHs1 were resistant to tetracycline, a commonly used antibiotic in feedlots, and had Cu and Zn MIC higher than 1 mM. Since Cu and Zn are routinely used in feedlots, there is the possibility of co-selection of AMR in H. somni due to selection pressure created by Cu and Zn. Based on results of in-vitro conjugation experiments, ICEHs1 mediated transmission of antimicrobial and metal resistance genes is possible between BRD pathogens in the respiratory tract, potentially undermining treatment options available for histophilosis and BRD.